2007
DOI: 10.1002/dneu.20584
|View full text |Cite
|
Sign up to set email alerts
|

Effect of astrocyte‐targeted production of IL‐6 on traumatic brain injury and its impact on the cortical transcriptome

Abstract: Interleukin-6 (IL-6) is one of the key players in the response of the brain cortex to injury. We have described previously that astrocyte-driven production of IL-6 (GFAP-IL6) in transgenic mice, although causing spontaneous neuroinflammation and long term damage, is beneficial after an acute (freeze) injury in the cortex, increasing healing and decreasing oxidative stress and apoptosis. To determine the transcriptional basis for these responses here we analyzed the global gene expression profile of the cortex,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
25
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 35 publications
(28 citation statements)
references
References 95 publications
3
25
0
Order By: Relevance
“…2). Previous studies demonstrate IL-6-induced cell proliferation in several cell types [8,9,16,17]. In addition, brain injury-induced reactive gliosis and MPTP-induced microgliosis declined in IL-6 KO mice [18,19].…”
Section: Discussionmentioning
confidence: 88%
“…2). Previous studies demonstrate IL-6-induced cell proliferation in several cell types [8,9,16,17]. In addition, brain injury-induced reactive gliosis and MPTP-induced microgliosis declined in IL-6 KO mice [18,19].…”
Section: Discussionmentioning
confidence: 88%
“…Corresponding to the results seen in IL-6 knockout mice, GFAP-IL-6 mice, which overexpress IL-6 in the CNS, showed faster recovery and healing after TBI [215,216]. Transcriptome analyses of IL-6 knockout versus wildtype [217] and GFAP-IL-6 mice [218] post-TBI via cryoinjury, showed that multiple pathways involving inlammation, apoptosis and oxidative stress were afected by IL-6. For example, IL-6 knockouts had lower expression of the gene producing suppressor of cytokine signaling (SOCS), an inhibitory protein transcribed by the JAK/STAT pathway after IL-6 activation [217].…”
Section: Il-6 In Tbimentioning
confidence: 66%
“…brain-derived neurotrophic factor, early growth response 1) post-injury [217]. Injured GFAP-IL-6 mice expressed higher levels of complement component 4 and other inlammatory mediator genes in addition to lower levels of select pro-apoptotic genes and oxidative stress-related genes in comparison to injured wildtype mice [218].…”
Section: Il-6 In Tbimentioning
confidence: 99%
“…IL-6 KO mice had a substantially different response at 1 day after injury compared to WT controls, with a tendency for attenuated upregulation of multiple transcription factors; the authors suggest it is this early transcriptional difference that underscores the later poor recovery from TBI [86] . Mice producing IL-6 in astrocytes had increased expression of inflammatory genes compared to WT controls, as expected; they also had decreased expression of pro-apoptotic genes and changes in genes associated with a wide range of processes including oxidative stress, synaptic activity, and cell migration and proliferation [87] , thus demonstrating the pervasive nature of IL-6 signalling following injury. In another example, recent studies have conducted microarray analyses of TBI using mouse models of Alzheimer's disease [88,89] .…”
Section: Traumatic Brain Injurymentioning
confidence: 70%
“…Two studies have examined the transcriptome response to cryolesion in mice which have altered levels of the cytokine interleukin-6 (IL-6), an inflammatory mediator known to have significant and wide-ranging effects on the response to neurotrauma. The first used IL-6 KO mice which have a worse than usual response to TBI [86] , and the second used transgenic mice which produce IL-6 in astrocytes and are known to have less cell death and increased repair after TBI [87] . IL-6 KO mice had a substantially different response at 1 day after injury compared to WT controls, with a tendency for attenuated upregulation of multiple transcription factors; the authors suggest it is this early transcriptional difference that underscores the later poor recovery from TBI [86] .…”
Section: Traumatic Brain Injurymentioning
confidence: 99%